(untitled) (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2025)
A critical view of the place of Christian higher education in higher education systems The aim of the research on which this article reports is fourfold. The first aim is to investigate the question of whether the existence of Christian-based education is justified. The second is to investigate the geographic extent of Christian-based higher education. The third is to assess the quality of Christian-based higher education. The fourth aim is to synthesise and interpret all these from a South African perspective. The findings of the research are that, based on demographic and human rights considerations, a case could be made for the existence of Christian-based higher education institutions. Christian-based higher education institutions are widely distributed, and some of these institutions have made it to the list of the highest ranked universities. However, it is argued that there is a need to develop an all-encompassing instrument to assess the extent and depth or quality of Christian-based higher education institutions. On the evidence of this international survey, a case is made out for the existence of Christian-based higher education institutions in South Africa. It is recommended that such Christian-based higher education institutions in South Africa uncompromisingly strive for the dual aims of Christian philosophical and education quality.